Effects of exercise on muscle metabolites and sarcoplasmic reticulum function in ovariectomized rats - Gigli, Isabel (2002)
The relationships between exercise and metabolites as well as between exercise and sarcoplasmic reticulum function were studied in gastrocnemius muscle of ovariectomized-trained rats. Prolonged moderate-intensity exercise, treadmill up-hill run for 90 min with a 10 degree incline, decreased the muscle glycogen content. Exercise until exhaustion further lowered the glycogen concentration to 13% of the control, together with a significant decrease of ATP and glucose-6-phosphate concentrations. Also, Ag+-induced Ca2+ release, measured in whole muscle homogenate, showed a 30% reduction on exhaustion, while Ca2+ uptake was unaffected by this exercise. ATPase activities, of both homogenate and SR vesicles, and Ca2+ transport in the latter preparation were not altered on exhaustion. It could be concluded from these results that muscular fatigue in ovariectomized rats after aerobic exercise is caused by the change in energy supply and Ca2+ release from the SR, this latter possibly due to metabolites generated by the exercise.